(untitled) (Heritage, 2022)
We use Andrić’s posthumously published short story collection The House on Its Own (1976) to illustrate how the questions of artistic creation and identity are connected in this writer’s work. We interpret the collection in the context of Jung’s analytical psychology, Bakhtin’s idea of the polyphonic character of truth, Andrić’s own poetic writings from The Signs by the Road, and his short story Conversations with Goya whose theme and structure had already announced the narrative technique in The House on Its Own. We focused on this collection’s dominant narrative technique and its purpose. Each of the stories emerges from the meeting of two individuals: the writer/narrator and the character that confides in him. The writer embraces the characters, empathizes and comprehends through emotion the other and the different in them. At the same time, the characters resemble the narrator in having multilayered identities and feeling the need for overcoming their trivial everyday life. The narrator’s truth is subordinate to the characters’ stories: the validation of someone else’s words about oneself is simultaneously a validation of their personality and a form of self-validation. In The House on Its Own, the reader receives insight into the creative process itself and the role it plays in keeping these complex identities consistent. We point to the relation between Andrić’s creative technique in this collection and Jung’s technique of active imagination and we interpret the house on Alifakovac, in the spirit of Jungian analysis, as a metonymy for the narrator himself.